Unveiling the significance of TREM1/2 in hemorrhagic stroke: structure, function, and therapeutic implications - Kong, Yancheng; Wang, Di; Jin, Xu; Liu, Yi; Xu, Hui (Frontiers in Neurology, 2024)
Stroke has long been a major threat to human health worldwide. Hemorrhagic stroke, including intracerebral hemorrhage and subarachnoid hemorrhage, exhibits a high incidence rate and a high mortality and disability rate, imposing a substantial burden on both public health and the economy and society. In recent years, the triggering receptor expressed on myeloid cells (TREM) family has garnered extensive attention in various pathological conditions, including hemorrhagic stroke. This review comprehensively summarizes the structure and function of TREM1/2, as well as their roles and potential mechanisms in hemorrhagic stroke, with the aim of providing guidance for the development of targeted therapeutic strategies in the future.